ID 429 – Clinical and electrophysiological follow-up study of a patient with congenital myasthenic syndrome (CMS) associated with mutations in the gen of the agrin (AGRN). Issue 3 (March 2016) - Fernandez, J.M.; Mederer, S.; Diéguez-Varela, C.; Padrón, M.L.; Navarro, C.; Maselli, R.
Abstract : Objective: We describe the clinical and electrophysiological findings of a severe form of congenital myasthenic syndrome (CMS) caused by two heteroallelic mutations in the gene encoding agrin ( AGRN ). Patient and methods: A 43 year-old-man, born after a normal pregnancy at term, presented with generalized hypotonia in the first months of life. He walked at 12 months but soon developed ptosis, neck and truncal muscle weakness progressed slowly. There was arreflexia with flexor plantar responses. He never had sensory symptoms. Parents were normal; an older brother with a similar condition died at15. Electrophysiological investigations were performed on many occasions; blood count and chemistries of serum and CSF were normal. Antibodies against AChR, MuSK, and P/Q voltage-gated were negative. Results: NCS were normal. RNS (3 Hz) of the median nerve induced a 40% decrement in the Thenar CMAP that improved markedly after exercise and Neostigmine. SFEMG showed increased jitter and blocking. Ultrastructure of muscle showed small nerve terminals, simplified postsynaptic folds, and disruption of their architecture. Genetic analysis revealed a nonsense and a missense mutations in the gene encoding agrin ( AGRN ). Conclusion: These findings demonstrate that the AGRN mutations can cause a disruption of the architecture of the neuromuscular junction that results in a severe CMS.